Cobble circles and standing stones : archaeology at the Rivas Site, Costa Rica - Quilter, Jeffrey, 1949- (University of Iowa Press, 2004)
In this first-person tale of archaeological adventure in the tropical forest, Jeffrey Quilter tells the story of his excavation of Rivas, a great ceremonial center at the foot of the Talamanca Mountain range, which flourished between A.D. 900 and 1300, and its fabled gold-filled cemetery, the Panteón de La Reina. Beginning with the 1992 field season and ending with the last excavations in 1998, Quilter discusses Rivas' builders and users, theories on chiefdom societies, and the daily interactions and surprises of modern archaeological fieldwork.